Imaging of muscle injuries in sports medicine - Heiß, Rafael; Janka, Rolf Matthias; Uder, Michael; Hotfiel, Thilo; Gast, Lena; Nagel, Armin Michael; Roemer, Frank (Die Radiologie, 2023)
Background: Early diagnosis of muscle injuries is indispensable in order to initiate appropriate treatment and to facilitate optimal healing.Purpose: The aim of this review is to provide an update on imaging of muscle injuries in sports medicine with a focus on ultrasound and magnetic resonance imaging (MRI) and to present experimental approaches in addition to routine diagnostic procedures.Materials and methods: A PubMed literature search for the years 2012-2022 using the following keywords was performed: muscle, muscle injury, muscle imaging, muscle injury classification, delayed onset muscle soreness, ultrasound, MRI, sodium MRI, potassium MRI, ultra-high-field MRI, injuries of athletes.Results: Imaging is crucial to confirm and assess the extent of sports-related muscle injuries and may help establishing treatment decisions, which directly affect the prognosis. This is of importance when the diagnosis or grade of injury is unclear, when recovery is taking longer than expected, and when interventional or surgical management may be necessary. In addition to established methods such as B-mode ultrasound and H-1-MRI, individual studies show promising approaches to further improve the imaging of muscle injuries in the future. Prior to the integration of contrast-enhanced ultrasound and X-nuclei into clinical routine, additional studies are needed to validate these techniques further.Conclusion: B-mode ultrasound represents an easily available, cost-effective modality for the initial diagnosis of muscle injuries. MRI is still considered the reference standard and enables an accurate morphological assessment of the extent of the injury. There are still no imaging approaches available for the objective determination of the optimal point of return to play.
CRIS-Team WoS Importer:2023-03-24